397 Intra-tumor immunotherapy injections utilizing image guidance in interventional radiology: clinical trial experience at a tertiary care cancer center. (10th December 2020) - Murthy, Ravi; Sheth, Rahul; Tam, Alda; Gupta, Sanjay; Subbiah, Vivek; Janku, Filip; Yap, Timothy; Diab, Adi; Naing, Aung; Patel, Sapna; Meric-Bernstam, Funda
Abstract : Background: Image guided intra-tumor administration of investigational immunotherapeutic agents represents an expanding field of interest. We present a retrospective review of the safety, feasibility & technical nuances of real-time image guidance for injection & biopsy across a spectrum of extracranial solid malignancies utilizing the discipline of Interventional Radiology. Methods: Patients who were enrolled in image guided intratumoral immunotherapy injection (ITITI) clinical trials over a 6 year period (2013–19) at a single tertiary care cancer center were included in this analysis. Malignancy, location, imaging guidance utilized for ITITI & biopsy for injected (adscopal) & non-injected (abscopal) lesions were determined and categorized. Peri-procedural adverse events were noted. Results: 262 pts (146 female, 61 yrs median) participating in 29 immunotherapeutic clinical trials (TLR & STING agonists, gene therapy, anti CD-40, viral/bacterial/metabolic oncolytics) met study criteria. Malignancies included melanoma 88, sarcoma 32, colorectal 29, breast 23, lung 17, head & neck 15, ovarian 8, neuroendocrine 7, pancreatic adenocarcinoma 6, 3 each (cholangioCA, endometrial, bladder, GI tract), 2 each (RCC, thymicCA, lymphoma, merkel cell, prostate) & others 1 each (CUP, GIST, dermatofibrosarcoma, DSRT, neuroblastoma, thyroid). All 169 & 93 patients received the intended 1371 ITITI in parietal (abdominal/chest wall, extremity, neck, pelvis) or visceral (liver, lung, peritoneum, adrenal) locations respectively; 83 patients received lymph node injections within either location. Imaging guidance was US in 68% of the cohort (US 161, CT+US 19); CT was used in 30% (81) & MRI in 1 patient. Median diameter of the ITITI lesion was 32 mm (8–230 mm). Median volume of the ITITI therapeutic material/session was 2 ml (1–6.9 ml). Lesions were accessed using a coaxial technique. ITITI delivery needles used at operator preference & tailored to lesion characteristics were either a 21G/22G Chiba, 21G Profusion (Cook Medical), 22G Morrison (AprioMed), 25G hypodermic (BD) & 18G Quadrafuse (Rex Medical). 2840 core biopsies (>18G Tru-cut core, Mission, Bard Medical) were performed in 237 patients during 690 procedures; biopsy sessions were often concurrent & of the ITITI site. 137 patients also underwent biopsy of a non-ITITI site (89 parietal location). Dimensions of the non-ITITI lesion were median 10 mm (7–113 mm); US image guidance was used in 97 patients (72%) to obtain a total of 1257, >18G Tru-core samples. 1.3% of injections resulted in SAE (NCI CTC AE >3) and 0.5% of 4097 biopsies developed major complications (SIR Criteria); both categories were manageable. Conclusions: Utilizing real time image guidance, ITITI to the administration of a myriad of investigational immunotherapeutic agents with concomitant biopsy procedures to date are associated with a high technical success rate & favorable safety profile. Acknowledgements: Joshua Hein, Mara Castaneda, Jyotsna Pera, Yunfang Jiang, Shuang Liu, Holly Liu and Anna Lui Trial Registration: N/A Ethics Approval: The study was approved by Institution's Ethics Board, approval number 2020-0536: A retrospective study to determine the safety, feasibility and technical challenges of real-time image guidance for intra-tumor injection and biopsy across multiple solid tumors. Consent: 2020-0536 Waiver of Informed Consent Reference: Sheth RA, Murthy R, Hong DS, et al. Assessment of image-guided intratumoral delivery of immunotherapeutics in patients with cancer. JAMA Netw Open 2020;3(7):e207911. doi:10.1001/jamanetworkopen.2020.7911